IMPLEMENTATION OF DELETION OF VEHICLE NUMBERS OF UNREGISTERED TAXPAYERS AFTER THE VALID PERIOD OF THE VEHICLE NUMBER REGISTRATION CERTIFICATE EXPIRES IN PEKANBARU CITY BASED ON LAW NUMBER 22 OF 2009 CONCERNING ROAD TRAFFIC AND TRANSPORTATION - Tarigan, Dwi Franata; Asnawi, Eddy; Silm Oktapani, Silm (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2024)
ABSTRACTArticle 74 paragraph (2) letter b of Law Number 22 of 2009 concerning Road Traffic and Transportation, regulates the deletion of registration and identification of motorized vehicles by the police if the motorized vehicle owner does not re-register at least 2 years after the validity period expires. Vehicle Registration.